Hubungan Antara Job Insecurity dan Stres Kerja dengan Turnover Intention pada Karyawan - Siahaan, Sari Rahayu; Situngkir, Decy; Nitami, Mayumi; Wahidin, Mugi (Lontara Journal of Health Science and Technology, 2022)
Turnover intention is the attitude employees looking for other jobs by leaving company, causes are job insecurity and work stress. Hay Group Survey Result World 2010-2018, turnover increase was 12.9% in 2014. At PT. DNR Corporation West Jakarta in 2020 employee turnover 19 people (15.77%) and 2021 as 19 people (28.62%), meaning that employee turnover is high above 10% per year and 10 employees survey study intend to find other work 79%. Purpose to determine relationship between job insecurity and job stress with turnover intention. Research method is quantitative and cross sectional design. Location at PT. DNR Corporation West Jakarta, November 2021-August 2022. Population 96 employees and 10 employees has been survey study, so 96-10= 86 samples using total sampling. Research instrument by questionnaire with theoretical modifications Halimah et al.,(2016) namely thinking about leaving, looking for alternative, intentions to leave. Data analysis are univariate and bivariate with chi-square test. Result showed employees who turnover intention 54.7%. Employees who feel job insecurity 55.8%. Employees who experience job stress 60.5%. In conclusion, there is no significant job insecurity (p-value = 0.323) and turnover intention, there is a significant job stress (p-value = 0.002) and turnover intention.